2023
DOI: 10.20517/2394-5079.2023.23
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma tumor microenvironment highlighting fibrosis and matrix components

Abstract: Cholangiocarcinoma (CCA) is an extremely aggressive malignancy characterized by a very limited prognosis and scarce treatment options. The majority of patients are diagnosed at an advanced stage and do not qualify for potentially curative surgical treatments, making CCA an increasingly prevalent global challenge. CCA is characterized by a highly reactive desmoplastic stroma, with complex mechanisms underlying the mutual interactions between tumor cells and stromal compartment. This review focuses on the recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 137 publications
0
0
0
Order By: Relevance
“…A recent study confirmed that MASLD exacerbates cholangitis and promotes iCCA in mice [109]. iCCA is characterized by a highly reactive desmoplastic stroma with a complex mechanism underlying the mutual interactions between tumor cells and the stromal compartment [110]. Although the pathogenic mechanisms of MASLD-associated iCCA have not been elucidated, iCCA development in patients with metabolic syndrome is characterized by osteopontin overexpression in the tumor stroma [111].…”
Section: Masld-associated Iccamentioning
confidence: 91%
“…A recent study confirmed that MASLD exacerbates cholangitis and promotes iCCA in mice [109]. iCCA is characterized by a highly reactive desmoplastic stroma with a complex mechanism underlying the mutual interactions between tumor cells and the stromal compartment [110]. Although the pathogenic mechanisms of MASLD-associated iCCA have not been elucidated, iCCA development in patients with metabolic syndrome is characterized by osteopontin overexpression in the tumor stroma [111].…”
Section: Masld-associated Iccamentioning
confidence: 91%